Pengungkapan ESG atau Kinerja ESG: Sebuah Tinjauan Literatur Sistematis tentang Pengaruhnya terhadap Kinerja Perusahaan di Negara-Negara Berkembang - A. A. Rai Niti Darmika Sukawati (AKUNTANSI 45, 2026)
Environmental, Social, and Governance (ESG) has gained increasing attention as a strategic factor influencing corporate performance. However, empirical evidence on the ESG-firm performance relationship remains inconclusive, particularly in emerging markets. This study aims to systematically review the effects of ESG disclosure and ESG performance on firm performance in emerging markets. Using a Systematic Literature Review (SLR) approach, 22 empirical studies published between 2020 and 2026 were analyzed. The findings indicate that ESG disclosure demonstrates a more consistent positive relationship with firm performance than ESG performance itself. ESG disclosure is associated with improved firm value, profitability, financing access, and stakeholder trust through enhanced transparency and reduced information asymmetry. In contrast, ESG performance produces mixed results, ranging from positive and insignificant to negative effects depending on institutional conditions and implementation maturity. The review also highlights the importance of disclosure credibility, greenwashing risk, and non-linear ESG effects in explaining performance outcomes. Overall, the findings suggest that transparent and credible ESG disclosure serves as a more effective mechanism for value creation than ESG performance alone in emerging markets. The study provides implications for managers, investors, and future ESG research.